Optimization and Kinetic Elucidation of Cerbera Odollam (Sea Mango) Oil Fermentation into Polyhydroxyalkanoate (PHA) Polymer - Lim, Sook Wei (Curtin University, 2024)
This research project investigated the feasibility and mechanism of polyhydroxyalkanoate (PHA) production using the non-edible Cerbera odollam (locally known as sea mango) oil. Experimental results show that it is possible to produce PHAs from C. odollam oil via direct fermentation. A plausible PHA production mechanism from crude C. odollam oil in Pseudomonas resinovorans DSM 21078 was also established in this study. The process was accurately represented using the modified Monod-based and multi-scale kinetic models.